Incidence, risk factors, and outcomes of acute kidney injury among hiv positive medical admissions at the Bamenda Regional Hospital - Alex, Mambap Tatang; Carelle, Toukam Nguebmegne Arielle; Maimouna, Mahamat; Georges, Teuwafeu Denis; Enow, Ashuntantang Gloria (Journal of Clinical Nephrology, 2022)
Background: There is a paucity of data on the burden of acute kidney injury (AKI) in hospitalized HIV-infected patients in Sub-Saharan Africa in the “test and treat” era. Objectives: To study the incidence, risk factors, and outcomes of AKI among HIV-positive medical admissions in a secondary hospital. Materials and methods: We prospectively screened adult HIV-positive patients who gave their informed consent and were admitted to the Bamenda Regional Hospital for AKI from February to June 2020. We excluded participants with Chronic Kidney Disease (CKD) Stage 5 and those with confounders of serum creatinine. On admission and after 2-7 days, we extracted a venous blood sample from each participant to evaluate serum creatinine and diagnose AKI. The participants were then followed up on until they were discharged or died. We measured the need for dialysis, access to dialysis, and renal recovery at three months for patients with AKI. The amended KDIGO 2012 criteria were used to define and classify AKI. The University of Bamenda’s institutional review board provided ethical approval. Results: A total of 206 participants (39.8% men) were enrolled, with a mean (SD) age of 45.71(13.13) years. On enrolment, 89.8% (n = 185) of the participants were on combination antiretroviral therapy (c-ART), with 81.6% (n = 151) on tenofovir-containing regimens. The WHO HIV clinical stages 3 and 4 were present in 81.5% (n = 168) of the individuals. The most common reason for hospitalization was opportunistic infections (69.8%; n = 142). AKI was found in 30.6% (n = 63) of the patients, with 58.7% (n = 37) of them being classified as KDIGO stage 3. A total of 12 (42.9%) participants out of the 28 in need, were dialyzed. AKI was independently associated with use of traditional medicines (aOR = 2.9; 95% CI 1.4-6.3; p = 0.006), WHO HIV stages 3 and 4 (aOR = 4.1; 95% CI 1.1-15.7; p = 0.038), hypotension (aOR = 3.3; 95% CI 1.4-7.8; p = 0.008) and low haemoglobin level ≤ 8.0 g/dl (aOR = 3.5; 95% CI 1.7-7.4; p = 0.001). The AKI group used to have a significantly higher mortality rate (42.9% vs. 16.1%; p < 0.001). Renal recovery was complete in 66.7% of the 30 survivors at three months, partial in 13.3%, and no recovery in 20% of the survivors. Conclusion: Despite the growing use of combination antiretroviral medication, significant immunosuppression is still common in hospitalized HIV-positive patients, increasing the risk of AKI and worsening prognosis. In this high-risk population, early detection of AKI with renal function monitoring may improve results.